Pelatihan Olah Data dan Analisis Data Statistik Mahasiswa STISA Pamekasan melalui SPSS - Septi Dariyatul Aini; Sri Irawati (Universitas Mathla'ul Anwar Banten, 2021)
TRAINING OF PROCESSING AND ANALYSIS OF STATISTICAL DATA STUDENTS OF STISA PAMEKASAN WITH SPSS. This training was motivated because of the problems of the final semester students of STISA Sumber Duko Pakong Pamekasan in processing and analyzing data in quantitative research. Apart from the low basic abilities of students in calculating, this is also because the course material for the research methods they obtain is still general and leads more towards qualitative research; Most of the available examples of thesis are more likely to be qualitative research in nature. Through training in processing and analyzing statistical data with SPSS, it is hoped that it can help them understand how to process statistical data and interpret the output, as well as improve students' skills in processing statistical data using the help of SPSS statistical software. The flow of work stages in this training is: problem identification, selection of statistical data processing software, preparation of training materials, training, mentoring, and evaluation. The results of this training are: (1) the training participants gain new knowledge about statistical data processing and analysis using the SPSS software; (2) the training participants responded 100% positively to the training; (3) the training participants are very enthusiastic about the implementation of the training and are able to understand the training material very well. It can be seen that more than 50% of the training participants were able to complete statistical data processing with SPSS for different data and were able to analyze the SPSS output.